ANALISIS PENERAPAN ACTIVITY BASED COSTING SYSTEM DALAM MENENTUKAN HARGA POKOK PENJUALAN FOOD & BEVERAGE HOTEL BUMI SEGAH BERAU - Siti Munawaroh; Faisal Akbar Fathoni (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Ilmu Ekonomi (STIE) Pontianak, 2021)
This research is a qualitative descriptive research conducted at PT Bumi Segah Lestari. This research has three main objectives. First, it aims to determine the calculation of the cost of production using the traditional method used by the company. Second, to find out the calculation of the Cost of Production using the ActivityBased Costing System. Third, to find out the difference in the cost of production in the company using the traditional method and the Activity-Based Costing System.The data collection method used in this research is documentation. The object of research in this study is data related to the determination of the cost of production.Cost of Production with the traditional method obtained results for Chinese is Rp. 47,900.00 and for Whesternt is Rp. 67.99.00 while for Beverage is Rp. 29,800.00. Cost of Production using Activity-Based Costing System, the cost of production for Chinese is Rp. 60,457.00, for Whesternt is Rp. 65,522.00 and for Beveraga is Rp. 34,774.00.The results showed that the Activity-Based Costing System when compared with the traditional method gave greater results except for Whesternt. The difference that occurs is due to the imposition of overhead costs on each product. In the traditional method, the overhead costs for each product are only charged to one cost driver, namely the number of production units. In the Activity-Based Costing System, overhead costs for each product are assigned to several cost drivers so that the Activity-Based Costing System is able to allocate activity costs to each product appropriately based on the consumption of each activity.